Improving the efficiency of a photovoltaic converter using the maximum power point tracking method - Zibalov, D.; Sosnin, K. (Energy and Automation, 2025)
Methods and models of power consumption control systems for energy generation by solar photovoltaic converter (SPC) is an urgent task of finding the maximum power point (Maximum Power Point Tracking, MPPT) to increase efficiency. The results of mathematical numerical modeling in the MATLAB environment and experimental research using the physical model of SPC confirm the effectiveness of the developed control system. The input conditions included variable insolation, which was specified as a combination of two sinusoidal signals with an additional restriction within 200–1200 W/m², which allows modeling dynamic weather conditions, for example, the passage of clouds or partial shading. During the simulation, the voltage and current on the load were calculated through the conditional linear equivalent of the SPC taking into account the load resistance, which was changed according to the Perturb and Observe (P&O) algorithm. The developed system provides maximum power support throughout the entire simulation period, which confirms the practical value of the system for controlling SPC in energy systems. Key words: solar photovoltaic converter, resistance, maximum power point, mathematical model, perturb and observe